PENGEMBANGAN MEDIA PEMBELAJARAN KIMIA BERBASIS ANDROID DENGAN PENDEKATAN STEM PADA MATERI HUKUM DASAR KIMIA - Siagian, Louis Gustavo; Sugiharti, Gulmah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This Research and Development (R&D) study aims to develop an Android-based chemistry learning media using the STEM (Science, Technology, Engineering, and Mathematics) approach on the topic of Basic Chemical Laws, and to determine its feasibility and practicality. The development model employed was the 3D model, which is a modification of Thiagarajan’s 4D model, consisting of the Define, Design, and Develop stages. The product trial involved 25 students of class X-9 and one chemistry teacher at SMA Negeri 2 Medan. Data were collected using validation sheets completed by the teacher response questionnaire expert, the student response questionnaire expert, and the media expert, as well as by teacher and student response questionnaires. The results showed that the developed learning media achieved an overall feasibility percentage of 90.29%, categorized as Very Feasible. This percentage was obtained from the validation results of the teacher response questionnaire (expert: 90.32%), student response questionnaire (expert: 88.63%), and media expert (92.16%). The practicality test results indicated that the teacher response reached 91.13%. The student response reached 92.50%, both categorized as Very Practical Based on these findings, it can be concluded that the Android-based chemistry learning media integrated with the STEM approach on the topic of Basic Chemical Laws meets the criteria of being very feasible and very practical for use as a learning medium that supports both independent learning and classroom instruction.